2018
DOI: 10.3390/molecules24010092
|View full text |Cite
|
Sign up to set email alerts
|

A R2R3-MYB Transcription Factor, VvMYBC2L2, Functions as a Transcriptional Repressor of Anthocyanin Biosynthesis in Grapevine (Vitis vinifera L.)

Abstract: In grapevine, the MYB transcription factors play an important role in the flavonoid pathway. Here, a R2R3-MYB transcription factor, VvMYBC2L2, isolated from Vitis vinifera cultivar Yatomi Rose, may be involved in anthocyanin biosynthesis as a transcriptional repressor. VvMYBC2L2 was shown to be a nuclear protein. The gene was shown to be strongly expressed in root, flower and seed tissue, but weakly expressed during the fruit development in grapevine. Overexpressing the VvMYBC2L2 gene in tobacco resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…VvMYBC2L2 was a transcription repression MYB in grapevine. It had the highest expression in the green skin of the early stage of grapevine (Vitis vinifera 'Yatomi Rose'), and had the lowest expression in the red skin of the mature stage [33], which was consistent with the expression pattern of PqMYB4 in this study. However, PpMYB18 was a transcription repression gene found in peach, its expression pattern was different from the transcription repression genes above-mentioned.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…VvMYBC2L2 was a transcription repression MYB in grapevine. It had the highest expression in the green skin of the early stage of grapevine (Vitis vinifera 'Yatomi Rose'), and had the lowest expression in the red skin of the mature stage [33], which was consistent with the expression pattern of PqMYB4 in this study. However, PpMYB18 was a transcription repression gene found in peach, its expression pattern was different from the transcription repression genes above-mentioned.…”
Section: Discussionsupporting
confidence: 88%
“…Overexpression of VvMYBC2L2 in tobacco plants inhibited the accumulation of anthocyanins in corolla. Expression analysis showed that the expression of flavonoid-related genes NtCHS, NtDFR, NtLAR and NtUFGT in tobacco were significantly reduced [22,33]. The ectopic expression of the MYB transcription suppressor gene GbMYBF2 in Arabidopsis could inhibit the synthesis of anthocyanins and down-regulate the expression of structural genes CHS, F3H, FLS and ANS [35].…”
Section: Discussionmentioning
confidence: 99%
“…The MYBC2-L3 (VIT_214s0006g01620) is a transcriptional repressor in the anthocyanin synthesis [72]. In transgenic tobacco [73], VvMYBC2-L3 represses the DFR gene and might induce the expression of FLS, although this latter hypothesis was not confirmed. MYBC2-L3 was not DE in the current experiment, neither at T1 nor at T2, but is listed among the predicted targets of vvi-miR858 (Additional file 9).…”
Section: Biochemical and Molecular Data Support The Rootstock Effect mentioning
confidence: 99%
“…We found that MYB promoters harbored many elements related to abiotic and biotic stresses. For example, TC-rich repeats, which are reported to be involved in plant defense and stress responsiveness [33,34]; the promoter of VvMYBPA1 contains TC-rich repeats and can regulate flavonoid branching pathway to produce proanthocyanidins, which are potentially able to confer protection against various abiotic and biotic stresses [28,35]; WUN-motif was related to wound responsiveness [36]; the promoter of VvMYBC2-L2 contains WUN-motif element, which plays an important negative regulatory role in anthocyanin biosynthesis [37]; VvMYB14 and VvMYB15 contain WUN-motif element, which can strongly coexpress with STSs under a range of stress and developmental conditions, which is in agreement with the specific activation of STS promoters by these TFs [38]. The detailed information on the cis-elements of 134 R2R3-MYB transcription factors related to plant resistance can be found in Supplementary Table S1.…”
Section: R2r3-myb Transcription Factors Involved In Plant Defensementioning
confidence: 99%